"Reconstruction of Higher Education in India" - Athani, V. V. (Journal of Engineering Education Transformations, 2007)
The author Dr. V.C. Kulandaiswamy is an eminent academician, who has been the Vice Chancellor of three distinguished universities. He has come out with this highly thought provoking book based on his experience and contemplation.